Interleukin‐34 permits Porphyromonas gingivalis survival and NF‐κB p65 inhibition in macrophages. (27th May 2022) - Almarghlani, Ammar; Settem, Rajendra P.; Croft, Andrew J.; Metcalfe, Sarah; Giangreco, Matthew; Kay, Jason G.
Abstract: Interleukin‐34 (IL‐34) is a cytokine that supports the viability and differentiation of macrophages. An important cytokine for the development of epidermal immunity, IL‐34, is present and plays a role in the immunity of the oral environment. IL‐34 has been linked to inflammatory periodontal diseases, which involve innate phagocytes, including macrophages. Whether IL‐34 can alter the ability of macrophages to effectively interact with oral microbes is currently unclear. Using macrophages derived from human blood monocytes with either the canonical cytokine colony‐stimulating factor (CSF)1 or IL‐34, we compared the ability of the macrophages to phagocytose, kill, and respond through the production of cytokines to the periodontal keystone pathogen Porphyromonas gingivalis . While macrophages derived from both cytokines were able to engulf the bacterium equally, IL‐34‐derived macrophages were much less capable of killing internalized P. gingivalis . Of the macrophage cell surface receptors known to interact with P. gingivalis, dendritic cell‐specific intercellular adhesion molecule‐grabbing nonintegrin was found to have the largest variation between IL‐34‐ and CSF1‐derived macrophages. We also found that upon interaction with P. gingivalis, IL‐34‐derived macrophages produced significantly less of the neutrophil chemotactic factor IL‐8 than macrophages derived in the presence of CSF1. Mechanistically, we identified that the levels of IL‐8 corresponded with P. gingivalis survival and dephosphorylation of the major transcription factor NF‐κB p65. Overall, we found that macrophages differentiated in the presence of IL‐34, a dominant cytokine in the oral gingiva, have a reduced ability to kill the keystone pathogen P. gingivalis and may be susceptible to specific bacteria‐mediated cytokine modification. Abstract : Overview of changes within Interleukin‐34 (IL‐34)‐differentiated macrophages leading to altered interactions with Porphyromonas gingivalis . IL‐34 differentiation leads to increased dendritic cell‐specific intercellular adhesion molecule‐grabbing nonintegrin, compared to CSF1‐matured macrophages, as well as increased P. gingivalis survival, decreased NF‐κB p65 phosphorylation and subsequent decrease of IL‐8 production.